2018
DOI: 10.1210/en.2018-00320
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Calcification Is Regulated Via an miR-204/DNMT3a Regulatory Circuit Both In Vitro and in Female Mice

Abstract: Arterial calcification is a common cardiovascular disease that initiates from a process of osteoblastic differentiation of vascular smooth muscle cells (VSMCs). Accumulating evidence has demonstrated that microRNAs play an important role in regulating arterial calcification. miR-204 was significantly downregulated in calcified human renal arteries from patients with uremia; calcified arteries of mice, due to 5/6 nephrectomy with a high-phosphate diet (5/6 NTP); and in VSMCs induced by high phosphate concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 40 publications
2
52
0
Order By: Relevance
“…The expression of proteins was determined by Western Blot as previously described [3]. Brie y, the concentration of protein was detected using a BCA kit (Beyotime, Shanghai, China).…”
Section: Western Blot Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of proteins was determined by Western Blot as previously described [3]. Brie y, the concentration of protein was detected using a BCA kit (Beyotime, Shanghai, China).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Vascular calci cation is mainly characterized as the medial of aortic calci cation (termed as Mönckeberg's calci cation), and it often happens in patients with chronic kidney disease, especially end stage renal disease (ESRD) [1,2]. Lots of studies have demonstrated that vascular calci cation is not a simple passive process of calcium and phosphorus deposition but an active regulatory process, and the transdifferentiation of vascular smooth muscle cells (VSMCs) into osteoblast-like cells is regarded to be the key pathophysiological factor of vascular calci cation [3][4][5]. However, the speci c mechanism of vascular calci cation in patients with ESRD is still not entirely elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Mice were fed with 12‐hour daylight/darkness transition in Animal House of the Second Xiang‐Ya Hospital. To generate vascular calcification and ageing in mice, the 5/6 NTP mouse model was established following the procedure previously described . Briefly, 6‐week‐old C57BL/6 mice were treated with an intraperitoneal injection of pentobarbital sodium (50 mg/kg) to induce general anaesthesia before operation.…”
Section: Methodsmentioning
confidence: 99%
“…vascular calcification and ageing in mice, the 5/6 NTP mouse model was established following the procedure previously described. 28 Briefly, 6-week-old C57BL/6 mice were treated with an intraperitoneal injection of pentobarbital sodium (50 mg/kg) to induce general anaesthesia before operation. The anaesthesia state of the mice was validated frequently by loss of the pedal withdrawal reflex.…”
Section: Plasmid Constructs and Luciferase Reporter Assaymentioning
confidence: 99%
“…Among them, 15 (40.5%) have been confirmed or are suspected to promote or aggravate VC in different scenarios, while 22 (59.5%) protect against VC formation or progression. Direct gene targets have been identified for 14 miRNAs with negative VC regulatory capacity, including miR-29a/29b [14], miR-29b-3p [34], miR-30b [16,47], miR-30c [16], miR-30e [25], miR-34b/34c [29,64], miR-125b [13,22] miR-133a [19], miR-135a [30], miR-182 [42], miR-204 [15,41,50], and miR-205 [21], while few direct targets have been identified for miRNAs with VC enhancement ability (miR-34a [39], miR-128-3p [48], and miR-135a-3p [17]). In the following sections, we describe the clinical features of each VC-regulating miRNA based on their propensity for positive or negative vascular influences.…”
Section: Mirnas In Vc: Positive and Negative Vc Regulatorsmentioning
confidence: 99%